2020
DOI: 10.1002/chem.202000844
|View full text |Cite
|
Sign up to set email alerts
|

Hydrogen‐Atom Tunneling in Metaphosphorous Acid

Abstract: Metaphosphorous acid (HOPO), a key intermediate in phosphorus chemistry, has been generated in syn‐ and anti‐conformations in the gas phase by high‐vacuum flash pyrolysis (HVFP) of a molecular precursor ethoxyphosphinidene oxide (EtOPO→C2H4+HOPO) at ca. 1000 K and subsequently trapped in an N2‐matrix at 2.8 K. Unlike the two conformers of the nitrogen analogue HONO, the anti‐conformer of HOPO undergoes spontaneous rotamerization at 2.8 K via hydrogen‐atom tunneling (HAT) with noticeable kinetic isotope effects… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

5
4

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 74 publications
0
5
0
Order By: Relevance
“…have generated considerable scientific interest due to their potential as phosphorylation/phosphonylation reagents as well as their participation as intermediates/final products of combustion reactions involving warfare agents and flame retardants. , Dioxyphosphorane ( 1 , Figure ) and cis / trans -alkoxyphosphanone ( 2 , 3 ) are the structural isomers that these molecules are capable of adopting. The former, formally a P­(V) species, is thermodynamically more favorable for all species regardless of the nature of the R substituent , with the exception of the parent compound (i.e., R = H). In fact, parent dioxophosphorane 1a has been predicted to be more than 40 kJ/mol less stable than the cis-isomer of hydroxyphosphanone ( 2a ), and it was then not surprising that this least thermodynamically stable isomer (i.e., HPO 2 ) was only recently detected via infrared spectroscopy among several products formed during 193/266 nm laser photolysis of 2a in the Ar matrix at 2.8 K …”
Section: Introductionmentioning
confidence: 99%
“…have generated considerable scientific interest due to their potential as phosphorylation/phosphonylation reagents as well as their participation as intermediates/final products of combustion reactions involving warfare agents and flame retardants. , Dioxyphosphorane ( 1 , Figure ) and cis / trans -alkoxyphosphanone ( 2 , 3 ) are the structural isomers that these molecules are capable of adopting. The former, formally a P­(V) species, is thermodynamically more favorable for all species regardless of the nature of the R substituent , with the exception of the parent compound (i.e., R = H). In fact, parent dioxophosphorane 1a has been predicted to be more than 40 kJ/mol less stable than the cis-isomer of hydroxyphosphanone ( 2a ), and it was then not surprising that this least thermodynamically stable isomer (i.e., HPO 2 ) was only recently detected via infrared spectroscopy among several products formed during 193/266 nm laser photolysis of 2a in the Ar matrix at 2.8 K …”
Section: Introductionmentioning
confidence: 99%
“…The photolysis of cis ‐HOPO [9] in a solid Ar‐matrix was first performed by using a 266 nm laser. The resulting IR difference spectrum (Figure 1 A) shows the depletion of cis ‐HOPO (a, 3555.4/3548.4, 1252.6, 904.5, 841.5, and 523.9/517.4 cm −1 ) [9a] and the appearance of . PO 2 (d, 1325.6 cm −1 ) [22] .…”
Section: Figurementioning
confidence: 99%
“…Tunneling is a quantum mechanical phenomenon that describes how particles permeate through potential energy barriers. , The occurrence of tunneling in chemical reactions used to be largely ignored, and the conceptual framework to understand chemical reactivity has been inferred from the transition state theory (TST), which assumes that nuclei behave according to classical mechanics. , For many years, tunneling relevance to chemical reactivity has only been acknowledged in the field of chemical kinetics, where tunneling appears as a correction factor in the TST calculations of rate constants (in particular for reactions involving the transfer of hydrogen atoms or ions). , However, recent evidence has shown that tunneling not only is more common than previously thought (even occurring for reactions involving the motion of heavy atoms such as carbon) but also can have profound consequences on the chemical reaction outcome, casting doubts on the validity of the TST principles. …”
Section: Introductionmentioning
confidence: 99%